Simulation of the competition among traditional and on-demand software vendors. (January 2016) - Cocco, Luisanna; Concas, Giulio; Marchesi, Michele
In this work, we propose a simulation model to study the software market, and in particular the competition among on-premise and on-demand vendors of customer relationship management software. In this market two kinds of vendors, on-premise and on-demand vendors, and corporate customers interact. Vendors have an initial capital and a specific number of developers. They invest a fraction of their capital in their product quality and try to sell their products making a profit. Corporate customers buy software products for their employees, trying to minimize their cost and maximize their utility. The proposed model is able to reproduce the real trends of the market as regards both the price of software and the market shares of the vendors, despite there is relatively little empirical evidence available about the various mechanisms at play, and few experimental data. Our model could be used as a tool to forecast future market trends, or to plan business policies of investment and pricing. Any firm could calibrate this model depending on its past business trends in order to obtain simple guidelines to follow in the planning of business winning strategies.